A model of ripple formation on sloping beaches - Gunaranchithan, Veerasingham; Supbat Vongvisessomjai; Tawatchai Tingsanchali; Prida Thimakorn; Royal Government of The Netherlands (Bangkok : Asian Institute of Technology, 1982)
To observe the transient rate of the growth of a ripple and a fully developed ripple on a sloping bed, experiments· are carried out in a flume (40m x 1m x 1m). Two types of medium sand materials with median particle diameter 0.29 mm and 0.45 -mm are used. For coarser sand, a bed slope of 1/10 and 1/20 is used while for finer sand, 1/20 is used. The maximum particle velocity and excursion are calculated from small-amplitude wave equations. The experimental range of the water -wave characteristic for the sand is greatly reduced by the size limitations of the flume. A dimensional analysis is first made to find the predominant factors affecting the behaviour of ripple formation and these are, the relative smoothness of the bed sediment and the densiometric sediment Froude Number. Analyses of ripple formation and sediment transport from an initially sloping bed based on the obtained experimental results and on continuity equation of sediment transport are then followed. Empirical equations are obtained for the transient and fully developed ripple height and length. It is found that the ripple height and length depend only on water particle excursion for low bed velocity and depend on densiometric Froude Number for high bed velocity. Ripple skewness is related to the velocity asymmetry in dimensionless form. An expression is derived for the transport of sediment related to the ripple parameters. Due to the difficulty in analyzing, the ripple celerity involving in this equation is not evaluated empirically in respect to time.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Slopes (Soil mechanics); Ripple-marks